Peer Education Strategy Through the Utilization of Information Technology Media in Effectiveness of New Normal Policies as An Efforts to Control Covid-19 Pandemic - Sutrisno; Eko Sulistiono; Anajeng Esri Edhi Mahanani (Nusantara Science and Technology Proceedings, 2020)
2020 is a test year for each country globally. The Covid-19 pandemic is a scourge from various sides/fields of life in society, nation, and state. In Indonesia, the impact of the Covid-19 pandemic has been felt in the health, economy, even social and policy sectors. The pandemic, which started at the end of 2019 until now, still leaves homework for various countries, including Indonesia, to immediately carry out countermeasures effectively and efficiently. The policy that will then be taken sees the condition that is still unstable, then leads to WHO recommendations, namely the application of the new normal, including in Indonesia. The policy New Normal which leads to encouraging the implementation of "normal" social, national, and state life and side by side with Covid-19 while still implementing strict health protocols, will not work optimally if the level of public awareness is not high. People who are not alert and vigilant and lead to apathy about the policies and conditions of Covid-19 will have an even bigger "iceberg" impact. This study aims to disseminate information through a peer education strategy with the help of information technology-based media related to the implementation of the policy New Normal in the response to Covid 19 in Indonesia. This socialization is packed with technological developments and a touch of humanism in society and industrial development 5.0. This research is expected to be a form of the contribution of UPN "Veteran" East Java to the local community, nation, and state. In particular, this is to help make the policy effective New Normal in dealing with the impact of Covid 19 in Indonesia.